The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10071-015-0931-8
|View full text |Cite
|
Sign up to set email alerts
|

Do as I … Did! Long-term memory of imitative actions in dogs (Canis familiaris)

Abstract: This study demonstrates long-term declarative memory of imitative actions in a non-human animal species. We tested 12 pet dogs for their ability to imitate human actions after retention intervals ranging from 1 to 24 h. For comparison, another 12 dogs were tested for the same actions without delay between demonstration and recall. Our test consisted of a modified version of the Do as I Do paradigm, combined with the two-action procedure to control for non-imitative processes. Imitative performance of dogs rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 25 publications
4
27
1
1
Order By: Relevance
“…In support of both of our predictions, we found that dogs were able to imitate when the imitation test was unexpected (although less successfully than when it was expected), and imitation success decreased quickly (i.e., fewer subjects imitated) with increasing retention interval (GLMM of imitation success, effect of test condition: c 2 2 = 14.7, p < 0.001; Table 1; Figure 2). A more rapid decay of dogs' memory as a result of incidental encoding was apparent when we compared imitation success after 1 min and 1 hr retention interval when recalling was unexpected (this study) with results of our previous studies, with similar conditions (also with 1 min and 1 hr retention intervals) but when the imitation test was expected [14,15] (Figure 2). When the recall test was expected, imitation success of dogs was not significantly different between immediate recall and recall after 1 hr delay [15].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In support of both of our predictions, we found that dogs were able to imitate when the imitation test was unexpected (although less successfully than when it was expected), and imitation success decreased quickly (i.e., fewer subjects imitated) with increasing retention interval (GLMM of imitation success, effect of test condition: c 2 2 = 14.7, p < 0.001; Table 1; Figure 2). A more rapid decay of dogs' memory as a result of incidental encoding was apparent when we compared imitation success after 1 min and 1 hr retention interval when recalling was unexpected (this study) with results of our previous studies, with similar conditions (also with 1 min and 1 hr retention intervals) but when the imitation test was expected [14,15] (Figure 2). When the recall test was expected, imitation success of dogs was not significantly different between immediate recall and recall after 1 hr delay [15].…”
Section: Resultssupporting
confidence: 80%
“…A more rapid decay of dogs' memory as a result of incidental encoding was apparent when we compared imitation success after 1 min and 1 hr retention interval when recalling was unexpected (this study) with results of our previous studies, with similar conditions (also with 1 min and 1 hr retention intervals) but when the imitation test was expected [14,15] (Figure 2). When the recall test was expected, imitation success of dogs was not significantly different between immediate recall and recall after 1 hr delay [15]. In addition, imitation success with expected recall was more than 2-fold compared to when recall was unexpected (binomial GLM of imitation success after 1 hr retention intervals, expected recall [from 15] versus unexpected recall [this study]: 83.3% versus 35.3%; c 2 1 = 7.0, p = 0.008, regression coefficient [B ± SE] for expectedness = 2.22 ± 0.93).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In fact, the evidence for dogs’ ability to learn through direct imitation is mixed; while there is ample evidence that dogs imitate the actions of human experimenters in behavioral copying tasks (e.g. Fugazza & Miklósi, ; Fugazza, Pogány & Miklósi, ), there is less clear evidence that dogs directly imitate human actions in instrumental learning tasks (e.g. Kubinyi, Topál, Miklósi & Csányi, ; Mersmann, Tomasello, Call, Kaminski & Taborsky, ; Miller, Rayburn‐Reeves & Zentall, ; Pongrácz, Bánhegyi & Miklósi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Il s'agit donc d'une mémoire à long terme du « quoi ». Ils sont ainsi capables d'imiter une action, réalisée par un homme (par exemple, toucher une cible avec le nez), et de la reproduire sur commande, quelques minutes, voire une heure, après la démonstration [23][24][25]. Au-delà du critère de durée, la mémoire à long terme est subdivisée en deux sous-types de mémoire : la mémoire explicite (ou déclarative), qui correspond au souvenir conscient.…”
Section: Les Mécanismes De Mémorisationunclassified